Three-Dimensional Numerical Analysis and Engineering Evaluation of Stilling Basin and Foundation Bedrock of Kala Hydropower Station, China - Xu, Jianjun; Cui, Zhihao; Qian, Kun; Sun, Xiang; Xu, Jie (Frontiers in Physics, 2022)
ng capacity of sericitized slate would generally meet the engineering requirements of stilling basin. Sericitized slate can be used as the foundation bearing layer of stilling basin. However, considering that the characteristics of sericitized slate is easy to weaken with water, it was suggested to carry out necessary foundation improvement for sericitized slate to strengthen its engineering mechanical properties. Kala reservoir is a large hydropower station, which will be built on the Yalong River in Sichuan Province, China. The topography and geomorphology at the project area of the hydropower station are characterized of high mountain and deep V-shaped valley, where the engineering geological conditions are very complex. The stilling basin of Kara reservoir is planned to be built on a weak rockmass called sericitized slate. Therefore, the safety of stilling basin structure has an important impact on the normal operation of Kara hydropower station. In order to evaluate the working state of the stilling basin structure, a three-dimensional geomechanical model of the valley, mountains and stilling basin structure of Kara reservoir was built. The three-dimensional finite difference method was used to simulate engineering and mechanical responses of the stilling basin structure and foundation rock mass under various working conditions. Based on the simulation results, the structural layout of stilling basin and the rationality of sericitized slate treatment measurements were verified, which provided a basis for the optimal design of stilling basin structure. It was determined that the foundation beari